A combination of assays reveals biomass differences in biofilms formed by Escherichia coli mutants - Sule, Preeti (2009)
AIMS: The aim of this study was to develop an assay system that can quantify the amount of biomass in biofilms formed by different isogenic mutants of an Escherichia coli K-12 strain. METHODS AND RESULTS: The reported assay, which is based on the BacTiter-Glo™ assay from Promega, uses bioluminescence to detect the intracellular concentration of ATP, which correlates with viable bacterial cell numbers. The quantitative data obtained with this ATP assay were compared to those obtained with the conventional crystal violet assay. As a qualitative control, scanning electron microscopy was performed. CONCLUSIONS: The ATP assay, the crystal violet assay, and scanning electron microscopy yielded similar results for six of the eight strains tested. For the remaining two strains, the images from the scanning electron microscopy confirmed the results from the ATP assay. SIGNIFICANCE AND IMPACT OF STUDY: The ATP assay, in combination with other quantitative and qualitative assays, will allow us to perform genetic studies on the regulatory network that underlies the early steps in E. coli biofilm formation.